Analysis of the Effect of Novel Coronavirus 2019 (Covid-19) Spreading Toward Sharia Stock Market in Indonesia - Arie Rachmat Sunjoto; Khoirul Umam; Miftahul Huda; Shafira Maisaroh Aribah (Universitas Darussalam Gontor, 2024)
The purpose of this research is to identify and analyze the influence ofthe spread of Novel Coronavirus 2019 (Covid-19), the policies of IndonesianGovernment during pandemic (i.e. work from home, large-scale social restrictions(PSBB) and community activities restriction enforcement (PPKM), the movementof FTSE 100 and Nasdaq Composite indexes on Islamic stock market inIndonesia (represented by the Indonesian Sharia Stock Index). This study utilizesthe Vector Error Correction Model (VECM), Impulse Response Function(IRF), and Forecast Error Correction Model (FEVD) approach, with the rangedata from September 2019 to November 2022. The results of this researchindicates that the VECM test showed that Covid-19 case in Indonesia and themovement of FTSE 100 had a significant positive effect on ISSI in the longterm. Meanwhile, in the short term, Covid-19 case in Indonesia and governmentpolicies have had a significant negative effect on ISSI. In the IRF test, this showsthat the Covid-19 case in Indonesia and government policies during pandemichave had a significant negative effect on ISSI. Conversely, the movement of theFTSE 100 and Nasdaq Composite Index has a significant positive effect on ISSI. In the FEVD test, it can be seen that the biggest contribution to ISSI shockmovement was the shock itself of 85.24% and was followed by governmentpolicies, the Covid-19 case, FTSE 100 and Nasdaq. This investigation use threevariables in order to search the effect of these factors on the movement ofsharia stock market in Indonesia. The stock market represented by IndonesianSharia Stock Index (ISSI).